2015
DOI: 10.1103/physrevlett.115.202501
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Spectroscopy of New Proton-Unbound IsotopesAr30andCl2

Abstract: Previously unknown isotopes30 Ar and 29 Cl have been identified by measurement of the trajectories of their in-flight decay products 28 S þ p þ p and 28 S þ p, respectively. The analysis of angular correlations of the fragments provided information on decay energies and the structure of the parent states. The ground states of 30 Ar and 29 Cl were found at 2.25 þ0.15 −0.10 and 1.8 AE 0.1 MeV above the two-and one-proton thresholds, respectively. The lowest states in 30 Ar and 29 Cl point to a violation of isoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…2p-radioactivity which is essentially the energetically allowed simultaneous two-proton emission is investigated by employing two simple and effective well established theoretical formalisms (i) Relativistic mean-field plus state dependent BCS (RMF+BCS) approach [32,33,34,35,36,37,38] and (ii) Macroscopic-microscopic approach (Mac-Mic) with Nilson Strutinsky (NS) prescription [30,39]. We calculate one-and two-proton separation energies of proton rich Mg, Si, S, Ar and Ca isotopes near proton drip-line and identify 19 Mg, 22 Si, 26 S, 30 Ar and 34 Ca as potential candidates of 2p-radioactivity in agreement with the available experimental data [20,21,31] for 19 Mg, 22 Si and 30 Ar. The structural evidences for the existence of halo are searched in the above identified 2p emitters within the RMF+BCS approach by investigating spatial density distribution, larger charge radius, wave functions and single particle energies that reveal a halo like structure of weakly bound protons which is the highlight of this work.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…2p-radioactivity which is essentially the energetically allowed simultaneous two-proton emission is investigated by employing two simple and effective well established theoretical formalisms (i) Relativistic mean-field plus state dependent BCS (RMF+BCS) approach [32,33,34,35,36,37,38] and (ii) Macroscopic-microscopic approach (Mac-Mic) with Nilson Strutinsky (NS) prescription [30,39]. We calculate one-and two-proton separation energies of proton rich Mg, Si, S, Ar and Ca isotopes near proton drip-line and identify 19 Mg, 22 Si, 26 S, 30 Ar and 34 Ca as potential candidates of 2p-radioactivity in agreement with the available experimental data [20,21,31] for 19 Mg, 22 Si and 30 Ar. The structural evidences for the existence of halo are searched in the above identified 2p emitters within the RMF+BCS approach by investigating spatial density distribution, larger charge radius, wave functions and single particle energies that reveal a halo like structure of weakly bound protons which is the highlight of this work.…”
mentioning
confidence: 65%
“…So far 2p-radioactivity has been observed in the decay of ground state 45 Fe [1,14], 54 Zn [15,16], 48 Ni [17,18], 67 Kr [19], 19 Mg [20], 30 Ar [21], 31 Ar * corresponding authors: Mamta Aggarwal, mamta.a4@gmail.com [22,23] 20 Mg [24,25,26], and excited states 22 Mg and 94 Ag (for 1p and 2p decay) [27,28] in experimental and theoretical [29,30] works have provided useful insights into this exotic decay mode of proton rich nuclei. Recent experimental observations of (i) β-delayed two-proton emission in the decay of 22 Si [31] (ii) 2p correlated emissions in 28,29 S but not in 27,28 P which indicated [8,9,10] that the diproton correlations may result from proton configuration in the initial state like 2p halo rather than the deformed orbit (iii) and the speculation [11] that the 2p halo plays an important role in the diproton emission, lack a precise theoretical description that has invoked the present study.…”
mentioning
confidence: 99%
“…The observation of 30 Ar and 29 Cl low-lying states, including their g.s., was reported in Ref. [12]. The assigned ground and first excited states of 29 Cl were found at 1.8 +0.…”
Section: Introductionmentioning
confidence: 56%
“…of 30 Ar was found to be at 2.25 +0. 15 −0.10 MeV above the 2p emission threshold [12]. A sophisticated data analysis together with theoretical investigations revealed that the g.s.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation